2011
DOI: 10.1007/s00158-011-0695-y
|View full text |Cite
|
Sign up to set email alerts
|

Fast orthogonal search (FOS) versus fast Fourier transform (FFT) as spectral model estimations techniques applied for structural health monitoring (SHM)

Abstract: In the last decade, structural health monitoring (SHM) systems became essential to accurately monitor structural response due to real-time loading conditions, detect damage in the structure, and report the location and nature of this damage. Spectral analysis using Fourier transform has been widely used in SHM. In this research, a novel approach for the characterization of in structure damage in civil structure is introduced. The target is to develop vibration-based damage detection algorithms that can relate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…FOS algorithm has a lot of practical applications including spectral model estimations, time series analysis and non-linear system control [19][20][21][22], and the proposed algorithm is based on FOS algorithm. The main goal of the proposed algorithm is to create a functional expansion of an input y(n) by choosing the best basis functions from all candidate functions P k (n), in order to minimize the mean squared error (MSE) between y(n) and the functional expansion.…”
Section: High Resolution Carrier Frequency Estimationmentioning
confidence: 99%
“…FOS algorithm has a lot of practical applications including spectral model estimations, time series analysis and non-linear system control [19][20][21][22], and the proposed algorithm is based on FOS algorithm. The main goal of the proposed algorithm is to create a functional expansion of an input y(n) by choosing the best basis functions from all candidate functions P k (n), in order to minimize the mean squared error (MSE) between y(n) and the functional expansion.…”
Section: High Resolution Carrier Frequency Estimationmentioning
confidence: 99%
“…Recently, several researchers introduced time-frequency representatives including the wavelet transform (WT) (Adeli & Jiang, 2006;Cruz & Salgado, 2009;Giurgiutiu & Yu, 2003;Guo & Kareem, 2016a;Khoa, 2013;Melhem & Kim, 2003;Nagarajaiah & Basu, 2009;Qiao et al, 2012;Spanos et al, 2007;Spanos & Failla, 2005;Staszewski & Robertson, 2007;Tang et al, 2010;Wong & Chen, 2001), the Fourier transform (FT), the short-time Fourier transform (STFT) (El Shafie et al, 2012;Giurgiutiu & Yu, 2003;Guo & Kareem, 2016a;Melhem & Kim, 2003;Nagarajaiah & Basu, 2009), the Hilbert transform (HT) (Feldman, 2014;Kunwar et al, 2013;Loutridis, 2004;Pines & Salvino, 2006;Roy et al, 2019;Salvino et al, 2003;Si et al, 2016) and the Wigner-Ville distribution (WVD) (Berinde et al, 2006;Bradford et al, 2006;G. Chen et al, 2013;Claasen & Mecklenbräuker, 1980;Guo & Kareem, 2016b;Martin & Flandrin, 1985;Tang et al, 2010;Wu & Chiang, 2009) as non-parametric system identification strategies (Salvino et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the usage of FT in system identification, El Shafie et al (El Shafie et al, 2012) found that the STFT cannot remain robust when the moving window length is too small. Using the STFT always requires a trade-off between time and frequency resolution due to Heisenberg's uncertainty principle.…”
Section: Introductionmentioning
confidence: 99%
“…Damage characterization from structural responses is a critical theoretical issue in the field of structural health monitoring (SHM) [1][2][3][4][5][6][7]. Various signal processing methods such as the Fourier transform, wavelet transform, time-frequency analysis and intelligent computation [4][5][6][7] have been widely used to extract damage features from structural responses.…”
Section: Introductionmentioning
confidence: 99%
“…Damage characterization from structural responses is a critical theoretical issue in the field of structural health monitoring (SHM) [1][2][3][4][5][6][7]. Various signal processing methods such as the Fourier transform, wavelet transform, time-frequency analysis and intelligent computation [4][5][6][7] have been widely used to extract damage features from structural responses. Unlike these existing methods, fractal dimension analysis, a newly emerging mathematical tool, has been adopted in recent years to extract damage features from structural vibrational responses [8][9][10].…”
Section: Introductionmentioning
confidence: 99%